Gacha Addiction and In-App Purchases: a Study on Genshin Impact Players in Indonesia - Cokki Cokki; Haris Maupa; Wanstum Wanstum; Syarifuddin Sulaiman (Faculty of Economics and Business Udayana University, 2025)
The purpose of this study was to examine the impact of gacha addiction and good price on the intention topurchase in-app items, with mobile game loyalty as a mediating variable. The research employed a quantitativeapproach using Partial Least Squares-Structural Equation Modeling (PLS-SEM) to analyze survey datacollected from 208 Genshin Impact players in Indonesia through random sampling and online questionnaires.The results indicate that gacha addiction significantly influences the intention to purchase in-app items, whilegood price has a moderate effect. Additionally, mobile game loyalty serves as a partial mediator in therelationship between gacha addiction and purchase intention.